Diversity of microbial communities in the rhizosphere soil of the transgenic (AtAREB1) and conventional (BR 16) soybean plants - Janaína Fernanda Catosso Maia; Alessandra Tenório Costa; Julio Cesar Polonio; João Lúcio Azevedo; Renata Fuganti-Pagliarini; João Alencar Pamphile; Alexandre Lima Nepomuceno (Acta Scientiarum. Biological Sciences, 2025)
Rhizosphere soil is one of the most diverse microbial environments worldwide and is recognized as an ecosystem undergoing continuous transformation. Microorganisms inhabiting the rhizosphere soil play diverse roles in maintaining and stabilizing the environment. Consequently, plant-associated habitats serve as a dynamic environment influenced by various microbial composition factors. Genetically modified plants have introduced numerous traits into agriculture to address productivity-limiting factors, such as drought. This study aimed to assess the microbial diversity in the rhizosphere soils of drought-tolerant transgenic (AtAREB1) and conventional (cultivar BR 16) soybean plants. Bacterial communities were investigated using a cultivation-independent approach, utilizing pooled samples from the respective soils, followed by pyrosequencing of the 16S rRNA gene. In addition, physicochemical parameters of the soils were evaluated. The results indicated that the microbial diversity in the rhizosphere soil of both transgenic and conventional plants remained unchanged, with similar taxonomic distributions observed in both bacterial communities. Analysis of physicochemical parameters in both soils suggested a potential direct relationship between these properties and the microbial community profile, with implications for soil nutrient content and physical composition. These results are positive for biosafety when using the transgenic cultivar compared with the conventional crop.